Development of A Learning Model For Basic Javaline Throwing Movements Through The Teaching Games for Understanding Approach - Syahruddin Syahruddin; Muhammad Syahrul Saleh; M. Sahib Saleh (UNIVERSITAS NEGERI MAKASSAR, 2023)
In general, this research and development aim to produce a learning model for basic javelin throwing movements using the TGfU approach for elementary school students. Apart from that, this research and development was carried out to obtain in-depth information about competencies, characteristics and initial abilities of elementary school students in implementing physical education learning, especially on learning material for basic javelin throwing movements. The design for research and development of this learning model uses Sugiyono's research and development approach model. Meanwhile, the subjects in this research and development were all 30 grade VI students at Mamajang I State Elementary School and Baddoka Makassar State Elementary School. The instruments used in this research and development are questionnaires and questionnaires which are used to collect data at stages: (1) needs analysis; (2) expert evaluation (initial product evaluation); (3) limited trials (small group trials); and (4) main trial (field test). To test the effectiveness of the model, a javelin-throwing process test and a rubric for assessing the correctness of the javelin-throwing movement were used. To see the results of the effectiveness of the model, a statistical test was used using the repeated observation t-test formula with a significance level of α = 0.05. Based on the development results, it can be concluded that: (1) Learning the basic javelin throwing movements through the TGfU approach using simple tools, namely the bombardier game for grade VI elementary school students is needed by Physical Education teachers; (2) overall this product is effectively implemented by Physical Education teachers in teaching basic javelin throwing movements to grade VI elementary school students; (3) Based on the results of the model effectiveness test, it has been empirically proven that the product results in the form of a learning model for basic javelin throwing movements for grade VI elementary school students have very good effectiveness.